(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article moves beyond theoretical literacy concepts to explore the practical, actionable strategies that proficient readers use to navigate a torrent of text. We will delve into how to set a purpose for reading, which dictates whether you skim, scan, or read closely. We will examine the power of annotation and note-taking to engage with and own the material.